2012
DOI: 10.1111/j.1740-1461.2012.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Race and Selective Enforcement in Public Housing

Abstract: Drugs, crime, and public housing are closely linked in policy and politics, and their nexus has animated several intensive drug enforcement programs targeted at public housing residents. In New York City, police systematically conduct “vertical patrols” in public housing buildings, making tens of thousands of Terry stops each year. During these patrols, both uniformed and undercover officers systematically move through the buildings, temporarily detaining and questioning residents and visitors, often at a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…This variable was constructed using race, age, education, public housing residence, and criminal justice history. Public housing was singularly important because it has been the locus of intensive police enforcement, and because the patrol tactics in those high‐rise buildings have been conducted in a manner different from patrols in other areas (Fagan et al ; Carlis ). The models included fixed effects for neighborhood and standard errors were clustered by neighborhood.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This variable was constructed using race, age, education, public housing residence, and criminal justice history. Public housing was singularly important because it has been the locus of intensive police enforcement, and because the patrol tactics in those high‐rise buildings have been conducted in a manner different from patrols in other areas (Fagan et al ; Carlis ). The models included fixed effects for neighborhood and standard errors were clustered by neighborhood.…”
Section: Resultsmentioning
confidence: 99%
“…One reason for stratifying and oversampling by neighborhood was the fact that there are strong differences in policing by neighborhood and race, especially with respect to proactivity, including stop and frisk activity (Fagan et al ; Geller & Fagan ; Fagan , ). This broader spatial pattern suggests that exposure to policing—specifically, to police stops—varies by race.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical research on banishment in public housing has been scant and has been focused on neighborhood‐level effects and comparisons. In recent studies, researchers have found that banishment increases trespass arrests and drug arrests with modest property crime reductions (Torres, Apkarian, and Hawdon, ), and that trespass enforcement has been concentrated in public housing communities disproportionately populated by racial minorities (Fagan, Davies, and Carlis, ). A few early public housing crime interventions did include banishment (Barbrey, ; McGarrell, Giacomazzi, and Thurman, ; Walsh et al., ), but such policies were part of larger crime reduction strategies within public housing, making it hard for evaluations to decipher the direct impact of no‐trespass policies on crime.…”
mentioning
confidence: 99%